[Nonruptured intracranial aneurysms: therapeutic recommendations] - Reith, W; Grunwald, I (2002)
With the development of new diagnostic noninvasive tools an increase in the diagnosis of asymptomatic nonruptured intracranial aneurysms has been shown. Physician and patient now have to decide wether to treat or to follow-up these aneurysms. This paper tries to review and to discuss the literature and to give guidelines for therapeutic decisions. The decision to treat an unruptured intracranial aneurysm must always comprise the individual factors such as age, life prognosis, neurological status, and the advantages and disadvantages of the considered method.